2015
DOI: 10.3122/jabfm.2015.02.140141
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of Care and Avoidable Hospitalizations for Chronic Obstructive Pulmonary Disease (COPD)

Abstract: Background: Numerous studied suggest that better continuity of care could result in better health outcomes. However, few studies have examined the relationship between continuity of care and avoidable hospitalizations.Methods: A retrospective cohort study design was adopted. We used secondary data analysis based on claim data regarding health care utilization under a universal coverage health insurance scheme in Tai

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 49 publications
2
45
1
1
Order By: Relevance
“…In studies focusing on adults or older people, low-income status was found to be adversely associated with health outcomes. 22,23 Despite the insignificance of enrollment in the P4P program, the program seemed to be one of the factors reducing the risk of asthma-related ED visits in older patients with asthma (aHR, 0.78). A study reported that P4P programs benefit patients with diabetes and improve COC as well as health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In studies focusing on adults or older people, low-income status was found to be adversely associated with health outcomes. 22,23 Despite the insignificance of enrollment in the P4P program, the program seemed to be one of the factors reducing the risk of asthma-related ED visits in older patients with asthma (aHR, 0.78). A study reported that P4P programs benefit patients with diabetes and improve COC as well as health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…An inverse association was reported between COC and health outcomes, such as hospitalization and ED visits, among patients with COPD. 22,25 In addition, asthma-COPD overlap syndrome has been increasingly discussed recently because of the similar clinical features of asthma and COPD. 48 Therefore, our results support the theory that older patients with asthma and COPD have a higher risk of ED visits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations